2005
DOI: 10.1095/biolreprod.104.039313
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and Its Antidepressant-Sensitive Transport in Mouse Cumulus-Oocyte Complexes and Early Embryos1

Abstract: Serotonin (5-hydroxytryptamine [5-HT]), is a neurohormone found in various nonneural tissues, including the gonads of many invertebrates, in which it regulates spawning and oocyte meiotic maturation. The possibility that a local serotonergic network might also exist in the female gonads of vertebrate species, including mammals, remains poorly documented. To clarify this possibility, we investigated mouse cumulus cells, oocytes, and embryos for three key serotonergic components, namely, 5-HT itself; the rate-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 40 publications
4
64
0
Order By: Relevance
“…This is similar to two previous reports where similar puncta were observed using anti-serotonin antibodies. However, both studies showed puncta with diffuse staining that could have been the result of fixation (Il'kova et al 2004, Amireault & Dube 2005. The fluorescent puncta we observed were not only diffuse but also did not have a vesicular shape.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…This is similar to two previous reports where similar puncta were observed using anti-serotonin antibodies. However, both studies showed puncta with diffuse staining that could have been the result of fixation (Il'kova et al 2004, Amireault & Dube 2005. The fluorescent puncta we observed were not only diffuse but also did not have a vesicular shape.…”
Section: Discussionmentioning
confidence: 53%
“…The antibody used in this particular study did not distinguish between TPH1 and TPH2 proteins. Another study failed to detect Tph1 transcripts in embryos and oocytes (Amireault & Dube 2005). This study did not, however, examine for Tph2 transcripts.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations